2(x-51)=36
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=\dfrac{36\cdot22\cdot51}{11\cdot17\cdot72}=\dfrac{1}{2}\cdot3\cdot2=3\)
35 \(\times\) 49 + 51 \(\times\) 36
= 35 \(\times\) 49 + 51 \(\)\(\times\) (35 + 1)
= 35 \(\times\) 49 + 35 \(\times\) 51 + 51
= (35 \(\times\) 49 + 35 \(\times\) 51) + 51
= 35 \(\times\)( 49 + 51) + 51
= 35 \(\times\) 100 + 51
= 3500 + 51
= 3551
\(\left(x+3\right)^2=36\)
\(\Rightarrow\orbr{\begin{cases}x+3=6\\x+3=-6\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x=3\\x=-9\end{cases}}\)
Vậy \(x\in\left\{3;-9\right\}\)
\(\left(x+5\right)^2=100\)
\(\Rightarrow\orbr{\begin{cases}x+5=10\\x+5=-10\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x=5\\x=-15\end{cases}}\)
Vậy \(x\in\left\{5;-15\right\}\)
\(\left(2x-4\right)^2=0\)
\(\Rightarrow2x-4=0\)
\(\Rightarrow2\left(x-2\right)=0\)
\(\Rightarrow x-2=0\)
\(\Rightarrow x=2\)
Vậy \(x=2\)
\(\left(x-1\right)^3=27\)
\(\Rightarrow\left(x-1\right)^3=3^3\)
\(\Rightarrow x-1=3\)
\(\Rightarrow x=4\)
Vậy \(x=4\)
35 x 49 + 51 x 36 = 35 x 49 + 51 x ( 35+1) =35 x 49 + 51 x 35 + 51 = 35 x ( 49 + 51 ) + 51 = 35 x 100 + 51 = 3500+51 = 3551
41 x 36 + 59 x 90 + 41 x 84 + 59 x 30
= 41 x (36 + 84) + 59 x ( 90 + 30 )
= 41 x 120 + 59 x 120
= 120 x ( 41 + 59 )
= 120 x 100
= 12000
4 x 51 x 7 + 2 x 86 x 7 + 12 x 2 x 7
= 7 x ( 51 x 4 + 86 x 2 + 12 x 2 )
= 7 x ( 204 + 172 + 24 )
= 7 x 400
=2800
41x 36 +59 x 90 +41 x84 +59 x 30
=41x (36+84) +59 x (90+30)
=41 x 120 + 59x 120
=120 x (41+59)
=120x 100
=12000
4x 51 x 7 + 2 x 86 x 7 + 12 x 2 x 7
=7x (51 x 4 + 86 x 2 - 12 x 2 )
=7x ( 204+ 172 + 24 )
= 7x 400
=2800
a: x-56:4=16
nên x-14=16
hay x=30
b: \(101+\left(36-4x\right)=105\)
\(\Leftrightarrow36-4x=4\)
hay x=8
Vì a: x-56:4=16
=>x-14=16
Hay:x=30
Vì b: 101+(36−4x)=105101+(36−4x)=105
⇔36−4x=4⇔36−4x=4
Hay:x=8
Vậy x={30:8}
Nếu sai thì thui nhá,đừng chửi mình!
36 . 46 + 54 . 64 + 51 + 49
= 36 . ( 46 + 54 ) + 64 . ( 51 + 49 )
= 36 . 100 + 64 . 100
= ( 36 + 64 ) x 100
= 100 x 100
= 10000
36 x 46 + 54 . 64 + 51 + 49
= 1656 + 3456 + 51 + 49
= 5112 + 51 + 49
= 5163 + 49
= 5212
Ủng hộ nha
=
`#3107.101107`
`1)`
`58 + 7x = 100`
`=> 7x = 100 - 58`
`=> 7x = 42`
`=> x = 42 \div 7`
`=> x = 6`
Vậy, `x = 6`
`2)`
`(x - 12) \div 12 = 12`
`=> x - 12 = 12*12`
`=> x - 12 = 144`
`=> x = 144 + 12`
`=> x = 156`
Vậy, `x = 156`
`3)`
`x - 56 \div 4 = 16`
`=> x - 14 = 16`
`=> x = 16 + 14`
`=> x = 30`
Vậy, `x = 30`
`4)`
`101 + (36 - 4x) = 105`
`=> 36 - 4x = 105 - 101`
`=> 36 - 4x = 4`
`=> 4x = 36 - 4`
`=> 4x = 32`
`=> x = 32 \div 4`
`=> x = 8`
Vậy, `x = 8`
`5)`
`2(x - 51) = 2*2^3 + 20`
`=> 2(x - 51) = 2^4 + 20`
`=> 2(x - 51) = 16 + 20`
`=> 2(x - 51) = 36`
`=> x - 51 = 36 \div 2`
`=> x - 51 = 18`
`=> x = 18 + 51`
`=> x = 69`
Vậy, `x = 69.`
1) 58 + 7x=100
7x = 100 - 58
7x = 42
x = 42 : 7
x = 6
2)(x-12):12=12
(x - 12) = 12 x 12
x - 12 = 144
x = 144 + 12
x = 156
3)x-56:4=16
x - 14 = 16
x = 16 + 14
x = 30
4) 101+(36-4x)=105
(36-4x) = 105 - 101
36-4x = 4
4x = 36 - 4
4x = 32
x = 32 : 4
x = 8
5)2(x-51)=2.2 mũ 3 + 20
2(x-51)=2.8 + 20
2(x-51)=16 + 20
2(x-51)= 36
x - 51 = 36 : 2
x - 51 = 18
x = 18 + 51
x = 69
2(x - 51) = 36
x - 51 = 36 : 2
x - 51 = 18
x = 18 + 51
x = 69
(x-51)=36:2
X-51=18
X=18+51
X=69
Vậy x=69